1998
DOI: 10.1007/pl00005210
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of interleukin-4 and interleukin-13 release from immunologically activated human basophils due to the actions of anti-allergic drugs

Abstract: Human basophils have recently been shown to rapidly produce and release interleukin (IL-)4 and IL-13 as well as histamine and eicosanoids. Since both IL-4 and IL-13 can initiate and maintain late phase allergic reactions we addressed whether some widely used anti-allergic drugs can inhibit the anti-IgE induced release of these cytokines from enriched human basophils. Basophils were enriched (47-92% purity) by Ficoll density centrifugation followed by elutriation and negative selection of contaminating cells us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…More recent studies have shown that the basophil is an important source of IL‐4 and IL‐13 ( Brunner et al ., 1993 ; MacGlashan et al ., 1994 ; Gibbs et al ., 1996 ; Redrup et al ., 1998 ; Shimizu et al ., 1998 ; Ochensberger et al ., 1999 ). The present study has shown that theophylline and IBMX are effective inhibitors of the stimulated generation of IL‐4 and IL‐13 from basophils, confirming observations made by others ( Shichijo et al ., 1997 ; Gibbs et al ., 1998 ). These data suggest that inhibition of PDE prevents not only the generation of histamine and leukotrienes from basophils but also cytokine generation as well.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have shown that the basophil is an important source of IL‐4 and IL‐13 ( Brunner et al ., 1993 ; MacGlashan et al ., 1994 ; Gibbs et al ., 1996 ; Redrup et al ., 1998 ; Shimizu et al ., 1998 ; Ochensberger et al ., 1999 ). The present study has shown that theophylline and IBMX are effective inhibitors of the stimulated generation of IL‐4 and IL‐13 from basophils, confirming observations made by others ( Shichijo et al ., 1997 ; Gibbs et al ., 1998 ). These data suggest that inhibition of PDE prevents not only the generation of histamine and leukotrienes from basophils but also cytokine generation as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little information regarding the effects of H 1 ‐antagonists on the generation of cytokines in basophils, or any other cell type. At least one study has reported moderate (50%) inhibition of IL‐4 and IL‐13 secretion in basophils using relatively high concentrations of the H 1 ‐antagonist, terfenadine [13]. However, this study did not probe into possible mechanisms responsible for this inhibition, including whether the concentrations of drug used were toxic.…”
Section: Introductionmentioning
confidence: 96%
“…Second‐generation H 1 antihistamines remain a cornerstone in the treatment of allergic rhinitis and urticaria [41, 42]. Some display anti‐inflammatory properties unrelated to H 1 receptor antagonism and mostly based on interference with the production and/or release of mediators such as histamine, cysteinyl leukotrienes, PAF and cytokines [9, 11–14]. However, the clinical relevance of these effects in vivo is presently unclear [43].…”
Section: Discussionmentioning
confidence: 99%
“…First‐generation antihistamines, like other related drugs, inhibit at low concentrations and enhance at high concentrations histamine release from the human lung [10]. Certain second‐generation antihistamines inhibit cytokine and histamine release from human basophils [11–14] and cysteinyl leukotriene C 4 (LTC 4 ) production from human basophils and eosinophils [11, 12] and suppress skin reactivity to platelet‐activating factor (PAF) [15], whereas others inhibit ICAM‐1 expression on epithelial cells [16] and reduce eosinophil infiltration during the late‐phase response [17]. These data indicate that antihistamines possess various anti‐inflammatory activities and that this property is not general to this class of compounds.…”
Section: Introductionmentioning
confidence: 99%